Impact of corporate social responsibility in the modern banking sector - Krishna, Anmol; Fičura, Milan; Drahokoupil, Jakub; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2023)
Corporate Social Responsibility (CSR) relates to a company's or organization's actions in its surroundings to address the identified, economic, social, & financial challenges. It is frequently characterized as a company that assesses, manages, and balances the economic, social, & environmental consequences of its operations. The amount to which a commercial entity should address environmental, ethical, & social issues in its activities by forsaking a part of its revenue for the society's benefit as a whole, the components of which include its workers, the climate, ethical and moral problems, and so on. Refusal to comply compromises the commercial future of a corporation. The ethical and moral model developed by Mahatma Gandhi in the 1930s, which recognized the responsibilities of family-run businesses involved in socioeconomic & economical activities, is widely recognized in India. There is no widely acknowledged definition of social responsibility for businesses. However, we might define it generally as a kind of ability to contribute made by companies out of their earnings to numerous facets of society's advancement. Whatever function corporations play in the domestic and global economies. They must respond to the socioeconomic needs of the communities in which they work. On the other hand, they must also satisfy the shareholders' time expectations. Banking is the backbone of any market world. It is a foundation of the banking markets and plays a key role in the success or failure of a business. India operates one of the world's most extensive banking systems, with these organizations largely focused on delivering economic services to the public while earning from their operations. They are not charitable organizations. They may be required, nevertheless, to fulfill corporate responsibility, accountability, and sustainability.
In a purely technical sense, we may argue that since banks operate in a community, they can address social issues by giving a small portion of their entire profit. Banks benefit not just from social reorganization but also from excellent branding as a result of their social efforts. Because it is widely understood that now every basic decision made by banks has an impact on the community & the ecosystem in a certain way. A firm's brand as well as marketing benefit from good CSR. When it comes to strategy, executing, and publicizing CSR operations, banks have organizational and financial constraints, according to a comprehensive review of the research from different publications, articles, research papers, and publications. Impact of Corporate Social Responsibility on The Modern Banking Sector- The goal of this study is to investigate and assess the perception, practice, implementation, and effect of corporate social responsibility among the selected banks in India. Some technologies and methodologies, including Microsoft Excel and JASP, were used to examine primary data collected via surveys, as well as CSR donations made during the past 7 years (secondary sources). The Indian banking industry is attempting to engage in Social responsibility via appropriate schemes; nevertheless, more focus is required on strategy development for new schemes, execution, reporting, and assessing CSR projects. The banking industry studied disregarding sectors including infrastructural development, economic and social causes, in addition to arts, music, athletics, and so on. and it is requested that the RBI adopt CSR criteria for all kinds of banks in India.
Vedoucí práce: Milan Fičura
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: finance and accounting [obor dipl. práce]; diplomové práce; master's theses